BRD4 Inhibition Attenuates Inflammatory Pain by Ameliorating NLRP3 Inflammasome-Induced Pyroptosis - Hua, Tong; Wang, Haowei; Fan, Xiaoyi; An, Ni; Li, Jian; Song, Honghao; Kong, Erliang; Li, Yongchang; Yuan, Hongbin (Frontiers in Immunology, 2022)
Chronic pain, such as persistent inflammatory pain, remains a public health problem which has no effective treatment at present. BRD4 inhibition, induced by JQ1 injection or BRD4 knockdown, has been used for attenuating inflammatory pain, however, the mechanism of which remains elusive. The aim of the present study was to explore the analgesic and anti-inflammatory effects of JQ1 injection and BRD4 knockdown in vitro and in vivo. JQ1 was intrathecally injected one hour before complete Freund’s adjuvant (CFA) administration, and mechanical and thermal hyperalgesia was measured on day 1, 3, and 7 after CFA administration. Western blot (WB) and immunofluorescence staining showed that BRD4 expression was increased after CFA administration and reached its peak on day 3. Immunofluorescence staining showed that BRD4 was mainly colocalized with NeuN-positive neurons in the spinal cord. CFA-induced inflammatory pain, paw inflammation and swelling was attenuated by JQ1-pretreatment. Interestingly, our study proved for the first time that NLRP3 inflammasome-induced neuron pyroptosis participated in inflammatory pain. The expressions of NLRP3, GSDMD-F, GSDMD-N, Caspase1-p20 and mature IL-1β were remarkably up-regulated on day 1, 3, 7 and peaked on day 3 after CFA injection. Immunofluorescence staining showed that GSDMD and Caspase1-p20 were colocalized with NeuN-positive neurons. BRD4 inhibition was able to decrease the expression of pyroptosis-related proteins through inhibiting the activation of NF-κB signaling pathway, both in vivo and in vitro. Taken together, BRD4 inhibition exerted analgesic and anti-inflammatory effects against inflammatory pain through the NF-κB/NLRP3/GSDMD/Caspase1 axis.